Analysis of Determinants Influencing the Demand for Cold Supply Chain in China’s Fresh Farm Produce Sector - Yuanyuan, Chen; Mohammad Affendy, Arip; Muhammad, Ali (Oxbridge Publishing House, 2024)
The significance of the cold supply chain arises from the perishable characteristics inherent in fresh agricultural goods. This investigation employs a static panel data model to scrutinize the variables impacting the demand for cold supply chain services concerning fresh agricultural produce within China. The research outcomes reveal that the factors influencing the demand for cold supply chain services for fresh agricultural produce in China comprise primary industrial value added, cargo turn- over, civilian freight vehicle ownership, household internet broadband access, and the ramifications of the COVID-19 pandemic. The study proposes specific developmental suggestions for enhancing the cold chain logistics infrastructure concerning fresh agricultural products in China, targeting these in- fluential variables, with the aim of elevating the overall standards of cold chain logistics for fresh agri- cultural produce and amplifying consumer well-being.